Comparison of Legionella longbeachae and Legionella pneumophila cases in Scotland; implications for diagnosis, treatment and public health response. Issue 2 (1st February 2016) - Cameron, R. L.; Pollock, K. G. J.; Lindsay, D. S. J.; Anderson, E.
Abstract : The reported incidence of Legionnaires' disease caused by Legionella longbeachae has increased since 2008 in Scotland. While microbiological and epidemiological studies have identified exposure to growing media as a risk factor for infection, little is known about the differences regarding disease risk factors, clinical features and outcomes of infection with L. longbeachae when compared with L. pneumophila. A nested case–case study was performed comparing 12 L. longbeachae cases with 25 confirmed L. pneumophila cases. Fewer L. longbeachae infected patients reported being smokers [27 % (95 % CI 2–52 %) vs. 68 % (95 % CI 50–86 %), P  = 0.034] but more L. longbeachae patients experienced breathlessness [67 % (95 % CI 40–94 %) vs. 28 % (95 % CI 10–46 %), P  = 0.036]. Significantly more L. longbeachae -infected patients received treatment in intensive care [50 % (95 % CI 22–78 %) vs. 12 % (95 % CI 0–25 %), P  = 0.036]. However, the differences in diagnostic methods between the two groups may have led to only the most severe cases of L. longbeachae being captured by the surveillance system. No differences were observed in any of the other pre-hospital symptoms assessed. Our results highlight the similarity of Legionnaires' disease caused by L. pneumophila and L. longbeachae, and reinforce the importance of diagnostic tools other than the urinary antigen assays for the detection of non- L. pneumophila species. Unfortunately, cases of community-acquired pneumonia caused by Legionella species will continue to be underdiagnosed unless routine testing criteria changes.